2014
DOI: 10.4184/asj.2014.8.6.813
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral Sagittal Alignment in Association to Intervertebral Disc Diseases

Abstract: Study DesignA cross-sectional case-control study was designed to compare the sagittal alignment of lumbosacral regions in two groups of patients suffering from low back pain, one with intervertebral disc pathologies and one without.PurposeTo evaluate the correlation between lumbosacral sagittal alignment and disc degeneration.Overview of LiteratureChanges in lumbar lordosis and pelvic parameters in degenerative disc lesions have been assessed in few studies. Overall, patients with discopathy were shown to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…A cross-sectional case–control study was designed by Habibi et al 36 in 2014 in order to evaluate the correlation between lumbosacral sagittal alignment and disc degeneration. They showed that the proposed global lumbosacral angle in the subject group was less than the control group, with the difference being statistically significant ( P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional case–control study was designed by Habibi et al 36 in 2014 in order to evaluate the correlation between lumbosacral sagittal alignment and disc degeneration. They showed that the proposed global lumbosacral angle in the subject group was less than the control group, with the difference being statistically significant ( P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…17,34,35 In recent years the MRI has become "gold standard" in diagnostic of the numerous pathological conditions of lumbar spine, including lumbar spinal stenosis, due to its possibility to visualize Roentgen-negative soft tissues. Standing MRI which was the alternative method to standing X-ray was not available in our center, so we chose the method of supine MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Hresko et al (2) stated that a high mean PI (78.9° (standard deviation (SD) 12.1°)) was noted in patients with high-grade spondylolisthesis. An association between abnormal sagittal alignment and LBP was also established (13,14).…”
mentioning
confidence: 88%